Comparison of Learning Method Effectiveness Between Jigsaw and Team Game Tournament on Achievement and Interpersonal Relationship Skill in Nursing Freshmen - Made Indra Ayu Astarini; Linda Juwita; Arif Helmi Setiawan (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2018)
Introduction: Evaluation results every semester about biochemical obtained by students the average value below 50. Cooperative learning method jigsaw and team game tournament (TGT) were an alternative learning method that can improved student learning outcomes. The purpose of this research was to understand the effectiveness of applied of jigsaw learning method compared to TGT to interpersonal relationship skill and achievement. Methods: This research used pre-experiment with research design Pretest-Posttest Comparison Group Design. Target population was all nursing students in two nursing institutions in Surabaya. Sample size were 208 chosen by total sampling. Independent variables were jigsaw and TGT and dependent variables were interpersonal relationship skill and achievement. Study instruments were interpersonal relationship skill questionnaire and objective test. Data analysis uses paired t test with α ≤ 0.05, prior normality test will be conducted. Results: Most respondents were 19 years old, single, female and lived with their parents. There was different result in student achievement between TGT and Jigsaw method (p = 0,005), TGT mean rank was 97,89 than jigsaw was 76,52. There was no different interpersonal relationship ability between TGT and jigsaw method (p = 0,263). Conclusions: TGT more effective than jigsaw to increase student learning achievement in biochemical. Those method has not different for student interpersonal relationship ability, because the student has been in good criteria for interpersonal relationship ability. Further implementation could be broad, other object in nursing could be the target, difficult subject would be underlined.